An action research partnership in an urban Texas county to explore barriers and opportunities for collaborative community health needs assessments - Nava, Marcela; English, Amanda S.; Fulmer, Linda; Sanchez, Katherine (Frontiers in Public Health, 2023)
The Affordable Care Act mandated triennial community health needs assessments (CHNAs) for greater nonprofit hospital accountability in responding to community health needs. Over ten years later, hospital spending on community benefits remains largely unchanged. While greater collaboration in CHNA implementation can increase hospital investment in community-based initiatives, nonprofit hospitals in conservative states are subject to policy, political, and economic factors that inhibit public health partnerships and magnify existing disparities in health care access. This participatory action research study explores the decision-making environment of collaborative CHNA implementation within a group of nonprofit hospitals in a north Texas urban county.In 2017 faculty from an urban anchor institution initiated an academic-community partnership with a coalition of nonprofit hospitals, public health departments, and academic institutions. An interdisciplinary research team engaged in multi-method document review and qualitative data collection to describe historical barriers for local CHNA processes and develop practical strategies for joint CHNA initiatives. Local CHNA documents were first reviewed through team-based content analysis and results applied to develop a qualitative study protocol. Key informants were recruited from county-based nonprofit hospitals, community-based nonprofit organizations, and public health systems. Seventeen senior-and mid-level professionals participated in semi-structured research interviews to describe their perspectives relating to CHNA-related planning and implementation decisions. Through iterative data collection and analysis, the research team explored CHNA-related knowledge, experiences, and processes. A constructivist lens was subsequently applied to examine historical barriers and future opportunities for local collaboration.Results: Findings reveal CHNA implementation is a multi-stage cyclical process in organizational environments with accountability to a wide range of public and private stakeholders. This promotes varied levels of inclusivity and conservatism in data collection and community benefit implementation. Decisions to collaborate are hindered by competing priorities, including compliance with existing guidelines, administrative simplicity, alignment with health care service delivery, and efficient resource use. Efforts to promote greater CHNA collaboration may be facilitated through intentional alignment with organizational priorities and clearly communicated benefits of participation for leaders in both public and private nonprofit health systems.Discussion: We consider implications for policymakers and health systems in restrictive political environments and advance a conceptual framework for greater CHNA collaboration.